Ethnic Disparities in Endothelial Function and Its Cardiometabolic Correlates: The Pathobiology of Prediabetes in A Biracial Cohort Study - Owei, Ibiye; Umekwe, Nkiru; Mohamed, Hanan; Ebenibo, Sotonte; Wan, Jim; Dagogo-Jack, Sam (Frontiers in Endocrinology, 2018)
Background: Endothelial function (EF) reflects the balance between vasodilatory and vasoconstrictive factors produced by (or acting on) the innermost lining of blood vessels. Endothelial dysfunction, an imbalance between these factors that favors vasoconstriction, has been associated with increased risk for cardiovascular (CV) disease. However, the influence of race/ethnicity and glycemic status on the association between EF and CV risk factors remain to be clarified. Subjects and Methods: We assessed EF in relation to glycemia and cardiometabolic profile in African American (AA) and European American (EA) offspring of parents with type 2 diabetes (T2D), who are participants in the prospective Pathobiology and Reversibility of Prediabetes in a Biracial Cohort (PROP-ABC) study. Assessments at enrollment included a 75-g OGTT, blood pressure, anthropometry, body composition (DEXA), and lipid profile. Other assessments were insulin sensitivity and resting energy expenditure (REE). Endothelial function was measured using flow-mediated vasodilation (EndoPAT 2000) and expressed as reactive hyperemia index (RHI). Results: We studied 190 subjects (100 AA, 90 C), mean age (± SD) 53.1 ± 9.1yrs and BMI 30.6 ± 6.8 kg/m2. Based on OGTT data, 96 subjects (52 AA, 44 EA) had prediabetes and 94 subjects were normoglycemic (48 AA and 46 EA). The RHI was lower in AA than EA (2.17 ± 0.55 vs 2.36 ± 0.72, P=0.05) and in prediabetic than normoglycemic subjects (2.14 ± 0.62 vs. 2.38 ± 0.65, P=0.013). Using RHI≤1.68 as diagnostic cut-off, 19% of participants with prediabetes and 10% of normoglycemic participants had endothelial dysfunction (P= 0.04). In univariate models, RHI was positively associated with age and HDL cholesterol levels, and inversely associated with adiposity, diastolic blood pressure, and 2hr plasma glucose. The association between RHI and adiposity was stronger in men than women. The associations between RHI and age, glucose and HDL cholesterol displayed marked ethnic disparities. Conclusions: In our biracial cohort comprising offspring of parents with T2D, prediabetes increased the risk of endothelial dysfunction. However, the association between EF and cardiometabolic risk factors was significantly modified by ethnicity and gender. Our findings support current understanding of endothelial dysfunction as an early sensitive indicator of cardiometabolic risk. Keywords: Prediabetes, Endothelial